التابعي صالح بن نبهان مولى التوأمة الجمحي بين الجرح والتعديل ودراسة مروياته الواردة في دواوين السنة والعلل - Al-Fayoumi | الفيومي, Ibrahim bin Fathi bin Muhammad bin Ramadan | إبراهيم بن فتحي بن محمد بن رمضان (Najran University | جامعة نجران, 2023)
Studying the opinions of the imams of discrediting and endorsement on, the successor, Saleh, the slave owned by Al-Tawama - who is one of the controversial narrators - and examining authentic opinions on his status and the aforementioned incapacitation, reinforced by exploring his narrations, and studying judgments passed by critical imams of the same | دراسة أقوال أئمة الجرح والتعديل في التابعي صالح مولى التوأمة –وهو أحد الرواة المختلف فيهم– وتحقيق الراجح في منزلته وما ذكُر من اختلاطه معززا ذلك بسبر مروياته، ودراسة أحكام الأئمة النقدية عليها